2011
DOI: 10.1016/j.tsf.2011.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Nano-structured morphological features of pulsed direct current magnetron sputtered Mo films for photovoltaic applications

Abstract: Nano-structured morphological features of pulsed direct current magnetron sputtered Mo films for photovoltaic applications, Thin Solid Films (2011Films ( ), doi: 10.1016Films ( /j.tsf.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Li et al 35 synthesized Q1D MoO 3 ribbon where the Raman peaks observed at 667 cm −1 , 819 cm −1 and 995 cm −1 are corresponding to the -MoO 3 . 36 37 The similar results were also observed by the Navas et al 25 in MoO 3 films. From Raman studies, it was conclude that, as the annealing temperature increased from 573 to 673 K the mixed phase of MoO 3 converted in to -MoO 3 .…”
Section: Raman Studysupporting
confidence: 73%
See 2 more Smart Citations
“…Li et al 35 synthesized Q1D MoO 3 ribbon where the Raman peaks observed at 667 cm −1 , 819 cm −1 and 995 cm −1 are corresponding to the -MoO 3 . 36 37 The similar results were also observed by the Navas et al 25 in MoO 3 films. From Raman studies, it was conclude that, as the annealing temperature increased from 573 to 673 K the mixed phase of MoO 3 converted in to -MoO 3 .…”
Section: Raman Studysupporting
confidence: 73%
“…The as-deposited molybdenum films showed a peak at 2 = 40 3 related to the (110) reflection of metallic Mo with polycrystalline nature. Karthikeyan et al 25 showed similar (110) reflection of molybdenum metal films achieved by pulsed DC magnetron sputtering technique. When the films annealed at 473 K the crystallinity of the metallic molybdenum increased and no reflection observed related to molybdenum oxide.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The diffusion trace of sodium can be controlled by modifying the molybdenum layer thickness, the grain density, and by a diffusion barrier to the glass. 32 Molybdenum can be obtained by pulse direct current magnetron sputtering, 33 thermal evaporation 34 and e-beam evaporation. 35 The DC sputtering is considered a suitable technique for deposition of Mo membrane of which will meet the requirements in solar cell development.…”
Section: Introductionmentioning
confidence: 99%
“…CIGSbased solar cells have achieved a record efficiency of 20% at the laboratory scale [4]. Recently, scientific and technologic research efforts have been focused on the deposition of CIGS absorbers with low cost single step methods [5,6]. The single step deposition process may cut down the costs of absorber film manufacturing as compared with the complex multi-step processes involved in the traditional deposition techniques.…”
Section: Introductionmentioning
confidence: 99%